Organizational Culture Influence On Total Productive Maintenance (TPM) and Operational Performance Using RASCH Model Analysis - Yusoff, Rushami Zien; Mohd Asaad, Mohd Norhasni (The Asian Journal of Technology Management (AJTM), 2013)
Abstract. Market globalization, competitive product and services, high economic crises are the most critical factors that influence the success of the manufacturing companies in global market. Therefore it is critical to the manufacturing companies to be efficient in production and lean tool may used to achieve that.  The most frequently used is the Total Preventive Maintenance (TPM), even though there are many studies have been conducted in relation to the TPM but there is limited research in investigating the effects of the TPM on operational performance. However, the result of the studies was not consistent, where TPM practice may have positive and negative impact on operational performance. Among the reason is the culture of the organization that influenced the implementation of TPM and operational performance. Due to that this study attempts to investigate the influence of organizational culture on the TPM implementation and operational performance.  Rasch model is used in this study due to its ability in interpreting and analyzing the ability of respondents in performing the difficult items. The online questionnaires were distributed to 63 randomly selected automotive companies located at Northern Region of Malaysia.  Results of the study revealed that the organizational culture has influenced on the successful implementation of TPM and operational performance. Therefore by the implementation of TPM in outstanding organizational culture can improve operational performance.   Keyword: Total Preventive Maintenance (TPM), Lean manufacturing, Operational performance, Organizational culture, Rasch modeldoi:10.12695/ajtm.2013.6.2.2How to cite this article:Mohd Asaad, M.N and Yusoff, R.Z. (2013). Organizational Culture Influence On Total Productive Maintenance (TPM) and Operational Performance Using RASCH Model Analysis . The Asian Journal of Technology Management 6 (2): 72-81. Print ISSN: 1978-6956; Online ISSN: 2089-791X.  doi:10.12695/ajtm.2013.6.2.2